Study of the Transit Oriented Development (Tod) Area of Jaticempaka, Pondok Gede District, Bekasi City - Bagawat Sari, Fauziya (Publisher Cv. Inara, 2023)
The City of Bekasi has a population of 2.5 million people in 2020 making the City of Bekasi dense, so it is necessary to improve the spatial planning system, including the modal transportation planning system.Along with the development of the Greater Jakarta area which was influenced by developments in Jakarta in the surrounding cities. With the existence of a National Strategy Project in Bekasi City such as DDT (Double-double Track) and LRT (Light Rail Transit) which have the potential to become a TOD (Transit Oriented Development) area.With the construction of the LRT station and the existence of the Jaticempaka TOD location which is directly adjacent to DKI Jakarta, the direction of economic activity development in the future has a tendency to develop regional and city scale economic activity functions, so that the development direction of the Jaticempaka TOD has a tendency to be developed into a large-scale TOD. sub-central services.Thus, the community can increase their choice of public transportation modes and facilitate access to destinations, as well as accommodate the needs of the community to pursue a cycle of activities within and outside the City of Bekasi. The purpose of the activity is to prepare a Study on the Study of the Transit Oriented Development (TOD) Area of ??Jaticempaka, Pondok Gede District, Bekasi City.